(untitled) (Castilla. Estudios de Literatura, 2021)
This article refutes the approach accepted by the critics to define the figure of Richard, the protagonist of Crimen Legal (1886) by Alejandro Sawa. This has been seen as the first case of novelization of the born criminalby the Italian Criminal Anthropology, commanded by Cesare Lombroso, in light of his behavior, some physiognomic characteristics and family heritage.